Postharvest losses and changes in quality of vegetables from retail to consumer : a case study of tomato, cabbage and carrot - Munhuewyi, Karen (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScFoodSc)--Stellenbosch University, 2012.